2017
DOI: 10.1039/c6ra27979a
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ionic liquids on the growth and simultaneous xylanase production by Sporotrichum thermophile: membrane integrity, composition and morphological investigation

Abstract: Ionic liquids (ILs) are emerging as promising solvent systems for carrying out various biochemical reactions. (v/v) concentrations and the cellular response in this particular IL was comparable with that of a control. In order to explore the feasibility of using whole cells of S. thermophile in place of its crude xylanase, a study was conducted for in situ pre-treatment and saccharification of [EMIM][OAc] treated wheat straw and a high amount of reducing sugars were released as compared to controls. IL stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 51 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…S. thermopile growth and xylanase production in the presence of IL was previously studied in Emerson’s medium (Sadaf and Khare 2017). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…S. thermopile growth and xylanase production in the presence of IL was previously studied in Emerson’s medium (Sadaf and Khare 2017). …”
Section: Methodsmentioning
confidence: 99%
“…Myceliophthora thermophile ) is known to produce a number of industrially relevant enzymes such as xylanases, cellulases, phytases, esterases and pectinases (Singh 2016). To further explore the usefulness of using S. thermophile cells for IL-mediated saccharification, their stability in ILs has been previously studied (Sadaf and Khare 2017). In this work, it was observed that S. thermophile was able to grow profusely and produce xylanase in the presence of two most commonly used ILs, [EMIM][OAc] and [BMIM][MeSO 4 ], indicating high tolerance of the fungus towards these ILs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8,9 ] Recently, our group observed that the increasing trend of lipid accumulation with the application of ionic liquids (ILs). [ 10 ] With the advancement in proteomic and genomic analysis, it has been found that due to stress application, the metabolic flux shifted towards the accumulation of more lipid in the microbes. [ 11 ] ILs with their industrially supportive properties are extensively used as green solvents, however, their compatibility with microbes limits their use.…”
Section: Introductionmentioning
confidence: 99%